CALCULATION OF A FOUR-STORY BUILDING UNDER THE INFLUENCE OF SEISMIC FORCES USING LIRA 9.6 SOFTWARE (Spectrum Journal of Innovation, Reforms and Development, 2023)
When calculating the effect of seismic forces on a four-story building, the general data of the construction area, geometric indicators of the building, dynamic characteristics of the building, strength and mechanical indicators of construction materials were analyzed according to the norm.